Effect of (Sm, Co) co-doping on the structure and electrical conductivity of ZnO nanoparticles. (21st October 2020) - Almoussawi, Mohammed; Abdallah, A M; Habanjar, Khulud; Awad, R
Abstract: (Sm, Co) co-doped ZnO nanoparticles (Zn1−2x Smx Cox O), 0.00 ≤ x ≤ 0.06, have been prepared by the co-precipitation technique. The effect of the dopant ions Sm 3+ and Co 2+ on the structural, morphological, and electrical conductivity of ZnO has been studied. XRD analysis shows the substitution of Zn 2+ ions by the co-doping Sm 3+ and Co 2+ ions with the formation of secondary phases as Sm2 O3 and Co3 O4 upon 0.005 co-doping and above. Raman spectra showed the characteristic mode of the wurtzite structure of ZnO nanoparticles with a vibration assigned to the bound of Co with the donor defects at high doping level of (Sm, Co). The spherical morphology of pure ZnO is transformed into nanorods as the concentration of Sm 3+ and Co 2+ increases. From EDX spectra, it was shown that all samples exhibit an excellent compositional homogeneity that verifies the Sm and Co presence as real dopants in ZnO crystalline structure. FTIR spectra show one discrete peak at 417 cm −1 with another broad peak at 568 cm −1 corresponding to Zn–O stretching, which confirms the formation of the wurtzite structure of the samples. Photoluminescence studies reveal the existence of minor defects in the co-doped samples. The study proposes the suitable use of the samples in the high-efficiency UV light-emitting devices due to the intense UV peaks compared with the lower visible peaks. The excitation dependent PL spectra demonstrated a redshift with increasing the excitation wavelength accounting for the distribution of energetic species in the ground state. The DC electrical conductivity is enhanced with (Sm, Co) co-doping of x = 0.1 due to the formation of thermally activated donor levels.